The First Case of Native Mitral Valve Endocarditis due to Micrococcus luteus and Review of the Literature - Alisha Khan; Thu Thu Aung; Debanik Chaudhuri (Case Reports in Cardiology)
Gram-positive cocci species, notably Staphylococcus, Streptococcus, and Enterococcus account for 80 to 90% of infective endocarditis cases. HACEK microorganisms (Haemophilus spp., Aggregatibacter actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens, and Kingella kingae) account for approximately 3% of cases and Candida species account for 1-2% of cases. Micrococcus luteus is a rare cause of endocarditis. To our knowledge, only 17 cases of prosthetic valve endocarditis have been described due to M. luteus and a single case of native aortic valve endocarditis has been described. The following case is the only documented case of native mitral valve endocarditis. A review of the literature pertaining to Micrococcus endocarditis was performed to further characterize the entity.